2016
DOI: 10.1177/0040517516681958
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic evaluation of Struto nonwovens and their relationship with thermal properties

Abstract: This paper presents an experimental investigation on the sound absorption behavior and thermal properties of Struto nonwovens by establishing relationship between these properties. Seven Struto nonwoven fabrics were selected to examine the noise reduction coefficient (NRC) and average values of sound absorption coefficients (αtrue¯) as well as thermal properties, including thermal conductivity and thermal resistance. The Brüel and Kjær impedance tube instrument and Alambeta were used for the evaluation of acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…The thermal properties and sound absorption of high-loft nonwovens made by staple, hollow and bi-component polyester were reported in refs. [11,12] The results showed that high-loft polyester nonwovens result in a sound absorption that shows a strong correlation with their thermal resistance. In addition, it was concluded that polyester nonwovens show the best sound absorption performance with airflow resistivity of 6000 Pa s/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The thermal properties and sound absorption of high-loft nonwovens made by staple, hollow and bi-component polyester were reported in refs. [11,12] The results showed that high-loft polyester nonwovens result in a sound absorption that shows a strong correlation with their thermal resistance. In addition, it was concluded that polyester nonwovens show the best sound absorption performance with airflow resistivity of 6000 Pa s/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Fiber diameter improves the performance of fibrous sound-absorbing materials, increasing flow resistivity as shown in empirical models developed by multiple authors [ 18 , 63 , 64 , 65 ]. Therefore, fique fibers would make a superior raw material for acoustic absorption applications.…”
Section: Resultsmentioning
confidence: 99%
“…Average coir diameter showed to be slightly larger than fique, a two-sample t-test for equal mean was made, the p-value was 0.0064; therefore, the null hypothesis was rejected and, consequently, there is a significative difference between the diameter of both fibers. Fiber diameter improves the performance of fibrous sound-absorbing materials, increasing flow resistivity as shown in empirical models developed by multiple authors [18,[63][64][65]. Therefore, fique fibers would make a superior raw material for acoustic absorption applications.…”
Section: Density and Diameter Measurementsmentioning
confidence: 96%
“…Thus, the smaller fiber diameters in samples A, B and C could be one reason accounting for their better sound absorption performance. For high GSM fabrics (samples A, B and C) there are more fibers involved in the viscous losses and more acoustic energy is dissipated in the form of heat energy [27]. …”
Section: Sound Absorption Coefficientmentioning
confidence: 99%